The importance of language in the home for school‐age children with permanent hearing loss. (15th November 2013) - Vohr, Betty R; Topol, Deborah; Watson, Victoria; St Pierre, Lucille; Tucker, Richard
Abstract Aim To determine the characteristics of the natural spoken language environment associated with better language skills at school age of children with permanent hearing loss (HL) screened in a newborn hearing screen programme. Methods A language processor recorded language environment including child vocalisations (CVs), conversational turns (CTs), adult word count (AWC), percentage of language and percentage of silence in 23 children with HL and 41 hearing controls. Relationships of language environment scores with Reynell language scores were analysed. Results Children with HL had significantly lower Reynell comprehension scores (15–25 points; p = 0.0001) and expressive scores (7–12 points; NS) than hearing children. In regression analyses for the children with HL, after adjusting for age of entry to early intervention and stay in a NICU, every increase in ten percentage points of language in the home was associated with 7.2 points higher comprehension score (p = 0.027) and 9.99 points higher expressive score (p = 0.006). After adjusting for nonverbal intelligence, similar independent effects of the language environment on both comprehension (p = 0.027) and expressive scores (p = 0.006) were identified. Conclusion A rich language environment in the home is associated with better language abilities, which are necessary for academic success for children with permanent HL at school age.